Formaldehyde in dwellings: environmental contamination and some emission sources - Viegas, Susana (2011)
Nowadays, indoor air contamination is considered an important health issue considering that people spend most of their time indoors. In this context, formaldehyde is a pollutant of major concern and, recently, concentration results obtained in European dwellings reveal high concentrations and values related to negative health effects on occupants. The present exploratory study sought to provide information about formaldehyde concentrations in Portuguese dwellings. It studied formaldehyde presence in new dwellings and dwellings with occupation and included 6 units of each setting. For concentrations measure, it was used direct-reading equipment that detects formaldehyde concentration by photoionization. Temperature and relative humidity were also measured in accordance with International Standard ISO 7726:1998. In the case of new dwellings, in 3 units concentration values were higher than 0.08 ppm. In addition, in 4 units of the 6 dwellings with occupation, concentrations higher than this reference value were obtained. The development of this study permitted us to recognize some of the possible indoor emissions sources and to define several of the preventive measures that can be applied.